A Fast Distributed Mapping Algorithm - Kropf, Peter; Boillat, J. E. (: Springer, 1990)
Generating an efficient program for a parallel computer requires that the distribution of the processes on the processors comprising the parallel computer is most optimal. This paper presents a new method for a load balanced and communication optimized process distribution onto an arbitrary processor (network) topology. As opposed to many other approaches for this problem, the presented algorithm is fully distributed and based on a purely local method. It has shown to be much faster compared to the classical methods like simulated annealing, heuristic search, etc.
, 1990